Do dependent suppliers benefit from buying firms' sustainability practices?. Issue 4 (October 2019) - Sancha, Cristina; Wong, Christina W.Y.; Gimenez, Cristina
Abstract: In view of the limited understanding and research on the effect of sustainable supplier development practices on supplier performance, this study examines the impact that the implementation of assessment and collaboration practices have on supplier performance outcomes. In addition, we investigate the role that supplier dependence has on the performance outcomes of assessment on and collaboration with suppliers. Based on a sample of 129 Chinese manufacturing firms, we run a series of OLS regressions to test our theoretical models. The findings suggest that collaboration improves supplier performance, while assessment causes a deterioration. In addition, supplier dependence could be leveraged for suppliers to gain performance improvements through collaborative practices. Highlights: Assessment and collaboration should be considered as two separate practices in the study of sustainable SD. Collaboration with suppliers in sustainability issues improves the supplier performance. Assessing suppliers in terms of sustainability has a negative impact on supplier economic performance. Supplier dependability could be leveraged for suppliers to improve performance.